Precision of dairy farming: navigating challenges and seizing opportunities for sustainable dairy production in Africa - Tadele, Etsemeskel; Worku, Destaw; Yigzaw, Dessie; Muluneh, Teshager; Melese, Abebe (Frontiers in Animal Science, 2025)
Precision Dairy Farming encompasses applying sophisticated technologies and data-centric methodologies to enhance the efficiency, productivity, and sustainability of dairy production. The objectives of this review focus on the precision of dairy farming; exploring the role of Precision Dairy Farming in transforming Africa’s dairy sector, navigating challenges that hinder the adoption of Precision Dairy Farming in Africa, and seizing the opportunities that can be leveraged for sustainable growth in dairy farming. Precision Dairy Farming technologies include wearable sensors, automated milking systems, precision feeding systems (automated dispensers), automated environmental monitoring and cooling systems, milk analyzers and somatic cell counters, geospatial tools and GPS-Enabled Grazing Management, mobile apps for farm management and data analysis. According to different research results this technology adoption led to a 30% increase in milk yield, a 25% reduction in feed costs, and a 20% decrease in veterinary expenses. Also, it is important to improve animal health monitoring, enhance decision-making, reduce workloads, and enhance financial security. The precision of Dairy farming in Africa faces a range of economic, social, and environmental challenges that limit its growth potential, despite significant expansion opportunities. These challenges can be due to the high cost of technology, limited access to finance, infrastructural limitations, low digital literacy and limited training for farmers, data collection and management challenges, lack of adapted Precision Dairy Farming technologies for African conditions and policy and market Constraints making it hard for small farmers to adopt new tools and improve their productivity. Precision dairy farming have different opportunity such as, improving Animal health and welfare, empowering smallholder farmers with digital and mobile solutions, supporting economic growth and rural livelihoods, meeting the growing demand for dairy Products, driving sustainability and environmental protection, enhancing public-private partnerships and strengthening dairy market and supply chain resilience. By embracing Precision Dairy Farming technologies, investing in education, enhancing cooperative structures, improving market access, and supporting policy frameworks, stakeholders can collectively transform the dairy sector into a sustainable and resilient industry.